Cellular damages in the Allium cepa test system, caused by BTEX mixture prior and after biodegradation process - Mazzeo, Dânia Elisa Christofoletti [UNESP]; Fernandes, Thaís Cristina Casimiro [UNESP]; Marin-Morales, Maria Aparecida [UNESP] (Elsevier, 2011)
Petroleum and derivatives have been considered one of the main environmental contaminants. Among petroleum derivatives, the volatile organic compounds benzene, toluene, ethylbenzene and xylene (BTEX) represent a major concern due to their toxicity and easy accumulation in groundwater. Biodegradation methods seem to be suitable tools for the clean-up of BTEX contaminants from groundwater. Genotoxic and mutagenic potential of BTEX prior and after biodegradation process was evaluated through analyses of chromosomal aberrations and MN test in meristematic and F 1 root cells using the Allium cepa test system. Seeds of A. cepa were germinated into five concentrations of BTEX, non-biodegraded and biodegraded, in ultra-pure water (negative control), in MMS 4×10 -4M (positive control) and in culture medium used in the biodegradation (blank biodegradation control). Results showed a significant frequency of both chromosomal and nuclear aberrations. The micronucleus (MN) frequency in meristematic cells was significant for most of tested samples. However, MN was not present in significant levels in the F 1 cells, suggesting that there was no permanent damage for the meristematic cell. The BTEX effects were significantly reduced in the biodegraded samples when compared to the respective non-biodegraded concentrations. Therefore, in this study, the biodegradation process showed to be a reliable and effective alternative to treat BTEX-contaminated waters. Based on our results and available data, the BTEX toxicity could also be related to a synergistic effect of its compounds. © 2011 Elsevier Ltd.
Keywords: Chromosomal aberration; Genotoxicity; Micronucleus; Mutagenicity; Petroleum derivatives; Allium cepa; Biodegradation process; BTEX mixture; Cellular damage; Culture medium; Environmental contaminant; Genotoxic; Genotoxicities; Meristematic cells; Negative control; Permanent damage; Root cells; Synergistic effect; Test systems; Ultra-pure water; Benzene; Cell culture; Chromosomes; Degradation; Ethylbenzene; Groundwater; Groundwater pollution; Microbiology; Toluene; Toxicity; Volatile organic compounds; Xylene; Biodegradation; benzene; ethylbenzene; ground water; toluene; xylene; bioaccumulation; biodegradation; chromosome; groundwater pollution; monocotyledon; mutagenicity; petroleum; sampling; toxicity; toxicity test; volatile organic compound; cell damage; chromosome aberration; controlled study; culture medium; genotoxicity; micronucleus test; nonhuman; onion; Bacteria; Benzene Derivatives; Biodegradation, Environmental; Chromosome Aberrations; Mutagenicity Tests; Mutagens; Onions; Petroleum; Xylenes